Main controls on phoD-harboring bacterial community abundance, composition, and activity from oil-contaminated soils at the Changqing oilfield, Northwest China - Li, Dandan; Du, Xianyuan; Li, Xingchun; Zhang, Xinyu; Zheng, Jin; Chu, Qin; Qiu, Weiwen; Zhang, Hanyu; Wang, Qingwei (Frontiers in Microbiology, 2026)
BackgroundSoil phosphorus (p) availability limits the native microbial activity, which then inhibits the petroleum hydrocarbon biodegradation. Microbial communities harbouring the alkaline phosphatase (ALP) phoD gene (phoD-harboring bacteria community, hereafter) play the key roles in the regulation of P availability in soils. Nevertheless, the consequences of oil contamination on ALP activity and phoD-harboring bacterial community dynamics are poorly understood. It is necessary to assess phoD-harboring bacterial abundance, community diversity, and ALP activity in response to oil contamination. This information would be useful for formulating plans for future bioremediation processes.MethodsIn this study, we sampled the contaminated and uncontaminated soils in the area surrounding crude oil pumping wells at the Changqing oilfield. The Real-time Quantitative PCR (qPCR) was used to detect the abundance of phoD gene. The diversities and compositions of phoD-haboring microbial communities were illustrated via Illumina high-throughput sequencing. Coincident soil chemical properties (soil water content (SWC), total petroleum hydrocarbons (TPHs), total nitrogen (TN), soil organic carbon (SOC), total phosphorus (TP), nitrate (NO3--N), ammonium (NH4+-N), dissolved organic carbon (DOC), available phosphorus (AP)) and ALP activities were also quantified.ResultsWe observed that petroleum contamination markedly decreased the abundance, richness, and diversity of the phoD-harboring bacterial community but greatly enhanced the relative abundance of phoD-harboring Actinomycetia, Thermoleophilia, and Rubrobacteria (p < 0.05). The relative abundances of phoD-harboring Alphaproteobacteria, Betaproteobacteria, and Gammaproteobacteria showed an increasing tendency and then decreased as the oil contamination concentration increased (p < 0.05). The soil water, nutrient content [carbon (C), nitrogen (N), and phosphorus], and nutrient ratio were the crucial parameters influencing the phoD-harboring bacterial community responding to oil contamination. The activity of ALP was associated positively and negatively with the relative abundance of Betaproteobacteria and Rubrobacteria, respectively.DiscussionOverall, the oil pollution stress altered the abundance, richness and composition of the active phoD-harboring functional microbial community. A significant decline in ALP activity in the oil-contaminated soils was likely caused by reduced abundance and changes in the composition of the phoD-harboring bacterial community, which were strongly dependent on the available N and P contents.